The new urban aesthetic : digital experiences of urban change - Degen, Monica Montserrat; Rose, Gillian, 1962- (2021)
"Cities are key sites for the reproduction of global capitalism, and urban branding is central to this transformative dynamic. In the 21st century, cities are also being profoundly reconfigured by the deployment of many kinds of digital technologies. Both of these shifts entrain sensory bodily experiences. This digitally mediated reconfiguration of what cities feel like is what this book terms the new urban aesthetic. The book focuses on three examples of urban change in which digital technologies of different kinds were central: a large scale urban redevelopment in Doha, the retrofitting of Milton Keynes to become a smart city, and the cultural regeneration of Smithfield Market into the Culture Mile in London. Each case study focusses on a different kind of digital mediation, including the computer-generated images created to sell new urban developments, smart city phone apps, and Instagram posts about particular urban places. The book identifies three versions of the new urban aesthetic: glamorous, flowing, and dramatic. It shows how each of these organize sensory experiences through particular distributions of temporality and spatiality. As well as exploring the importance of sensory constellations in our digitally mediated cities, the book also offers ways to investigate their fragility and potential for subversion. The New Urban Aesthetic is essential reading for researchers and students in urban studies, architecture, digital studies, sociology, and human geography"--
Introducing the new urban aesthetic -- The new urban aesthetic : a conceptual framework -- The conceived aesthetics of urban redevelopment : the case of Msheireb Downtown, Qatar -- The perceived aesthetics of digital urbanism : feeling digital embodiment in smart Milton Keynes -- The lived aesthetic of urban social media : anticipating the Culture Mile's Future -- The new urban aesthic and its power -- Conclusion : the differentiation and potentialities of the new urban aesthetic.
Includes bibliographical references and index.
Keywords: Smart cities; Technology -- Social aspects; City and town life